Role of 5-HT1 receptors of accumbens shell arena upon ACPA-induced anxiolytic-like behaviors in rat - Keramati nojedehsadat, Marzieh; Oryan, Shahrbanoo; Zarrindast, Mohammad Reza; Babapour, Vahab (Archives of Advances in Biosciences, 2013)
Cannabinoids induce diverse responses on anxiolytic–like behaviors. Moreover some studies postulated that there is a close relationship between this system and serotonergic system upon cognitive process formation. Thus the aim of present study is investigation the possible role of 5-HT1 receptor on anxiolytic–like behaviors induced by ACPA in the elevated plus maze task (EPM). In the present study rats weighting 250–300g upon surgery bilateral guide cannulae were implanted to allow microinjection of ACPA (agonist CB1 receptor), CP94253 Hcl(agonist 5-HT1 receptor) alone and them interaction in the AcbSh. The data showed pretest AcbSh infusion of ACPA at doses of0.0002, 0.002, 0.02 and 0.2 μg/rat increased and decreased the percentage of open-arms time (%OAT) and percentage of Enclosed-arms time (%CAT), respectively as compared to control groups. Pretest AcbSh infusion ofCP94253 Hcl at doses of 5, 0.5 and 0.05 ng/rat, did not alter anxiety-like behaviors. In addition intra-AcbSh microinjection of subthreshold dose of CP94253 Hcl did not alter ACPA-induced anxiolytic-like behaviors. Our data suggest that activation of AcbSh 5-HT1 receptor did not involve in ACPA-induced behaviors in the EPM task.